Faktor-Faktor Risiko yang Mempengaruhi Kanker Paru-Paru dengan Menggunakan Analisis Regresi Logistik - Juwita Juwita; Nonong Amalita; Meira Parma Dewi (Journal of Mathematics UNP, 2021)
Abstract – Lung cancer is a disease with characteristic presence of uncontrolled cell growth in the lung tissue. If not treated, the growth of these cells can spread beyond the lung. So if it is not taken seriously, will be ensured with lung cancer longer will increase. The factors that affect the risk of lung cancer are age, gender, cigarette consumption and lung disease history, family history, and type of work. To determine the factors that most influence the risk of lung cancer will be established a model which can help the application of a causal relationship between two or more variables by using logistic regression analysis. Which aims to determine the factors that influence and determine the chances of each of the factors that affect the risk of lung cancer. Based on theresults of the study, the factors that affect the risk of lung cancerat the Hospital Dr. M. Djamil Padang is age cigarette consumption and lung disease history. If a personolder than 40 years, smokers and have a history of lung disease, the chances that a person will suffer from lung cancer increases.Keywords–lung cancer, risk factor, logistic regression analysis